Improving Reliability Calculations In Cellular Communications System Stations Using Fuzzy Logic - حبيب, علاء (Latakia University Journal -Engineering Sciences Series, 2025)
Reliability is one of the most important parameters studied in many modern engineering applications, especially critical applications (spacecraft - nuclear reactors - medical applications - communications...). Traditional methods for reliability calculations have suffered from difficulties related to collecting information and monitoring, as these methods require quantitative information about malfunctions and failures of the system (equipment) studied in order to calculate its reliability. In most of the targeted applications, collecting information is a difficult task due to the difficulty of monitoring. Accordingly, we relied on Artificial Intelligence techniques to avoid the aforementioned difficulties, and in our research, we relied on Fuzzy Logic technology (one of the artificial intelligence techniques) to find a general model for improving reliability calculations in electronic equipment in general, including communications system equipment. To ensure the effectiveness of this model, we conducted a realistic study of applying this model to cellular broadcast stations (Base Stations) and compared the results with results obtained in a previous study by studying the reliability of the same broadcast stations, but according to traditional methods for calculating reliability (Weibull Distribution).